Mengasah Karakter Santri Melalui Seni Teater pada Hari Santri Nasional - Anugrah, Reza; Ridho, Rosyid; Kurtubi, Kurtubi (Lembaga Publikasi Ilmiah Nusantara, 2025)
National Santri Day is an important moment to commemorate the role of santri (Islamic boarding school students) in preserving and developing religious, cultural, and national values. One way to strengthen the character of santri is through activities that support the formation of good personality traits, one of which is theater arts. This study aims to explore the role of theater arts in shaping and honing the character of santri, with a focus on the implementation of theater training during National Santri Day celebrations. The research employs a qualitative approach with a case study of several pesantren (Islamic boarding schools) that conducted theater training during National Santri Day. Data were collected through observations, interviews with participants and pesantren administrators, and documentation studies. The findings reveal that theater arts can serve as an effective medium for developing santri character traits such as discipline, teamwork, self-confidence, empathy, and courage. Through role-playing, improvisation, and self-expression, santri gain a deeper understanding of the values taught in pesantren and apply them in their daily lives. Furthermore, theater arts activities provide opportunities for santri to explore their talents and potential, ultimately enriching their spiritual and social experiences. This study concludes that theater training is a strategic effort to strengthen the character of santri in the modern era and can serve as an alternative character education activity that is both enjoyable and beneficial.